Development of a multi-stage continuous fermentation strategy for docosahexaenoic acid production by Schizochytrium sp. (December 2018) - Guo, Dong-Sheng; Ji, Xiao-Jun; Ren, Lu-Jing; Yin, Feng-Wei; Sun, Xiao-Man; Huang, He; Zhen, Gao
Highlights: Fermentation kinetics of DHA production using Schizochytrium sp. was developed. Growth-uncoupled DHA production by Schizochytrium sp. was studied. Multi-stage continuous fermentation prediction model was established and applied. The DHA efficient production was realized by multi-stage continuous fermentation. Abstract: Docosahexaenoic acid (DHA) has wide-ranging benefits for normal development of the visual and nervous systems in infants. A sustainable source of DHA production through fermentation using Schizochytrium sp. has been developed. In this paper, we present the discovery of growth-uncoupled DHA production by Schizochytrium sp. and the development of corresponding kinetic models of fed-batch fermentations, which can be used to describe and predict the cell growth and substrate utilization as well as lipid and DHA production. Based on this kinetic model, a predictive model of multi-stage continuous fermentation process was established and used to analyze, optimize and design the process parameters. Optimal predicted processes of two-stage and three-stage continuous fermentation were developed and verified in lab-scale bioreactor based on the predicted process parameters. A successful three-stage continuous fermentation was achieved, which increased the lipid, DHA content and DHA productivity by 47.6, 64.3 and 97.1%, respectively, compared with two-stage continuous fermentation.